Effectiveness of Breastfeeding Counseling Training to Improve Knowledge, Attitude, and Skill of Support Groups - Prihanti, Gita Sekar; Wilyani, Dwi; Hasna, Alifah; 'Aisy, Alberta Rohadatul; Kurniawan, Bagus Putra; Saputri, Dita Sulung; Tontowi, Maharani; Elfahmi, Meuthia Quin Lathiefa Geraldine; Mufida, Umi Arof Arum; Musa, Wellystianti Panca Ningrum Aprilia (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: WHO and UNICEF advocate exclusive breastfeeding for the first six months of baby’s life and continue with complementary foods for up to two years, supporting the 2030 SDGs target for optimal health during the first 1000 days. The success of exclusive breastfeeding is still limited in some areas; therefore, it is necessary to establish breastfeeding support groups. Effective breastfeeding also requires educational interventions that change attitudes, knowledge, and skills in breastfeeding support groups. This study aims to determine the effect of breastfeeding counseling training on the knowledge, attitude, and skills of breastfeeding support groups.Method: The study was conducted in three villages in the work area of the Pesantren (Islamic Boarding House) II Public Health Center Kediri: Jamsaren, Tosaren, and Pakunden villages. The study was administered from January to February 2020.  The sample was taken with Purposive Sampling, and the number of samples was 60, varying from pregnant women, nursing mothers, husband/family, cadres, and midwives. This study used a quasi-experiment with one group pre-test-post-test design where all respondents did a pre-test, got lactation counseling training, and then took a post-test. The questionnaire evaluated knowledge, attitudes, and skills, and assessed by modifying lactation counseling training observation sheets from WHO.Result: This study exercised a quasi-experimental model with one group pre-test-post-test design. Data were analyzed univariately, while comparative testing was carried out bivariate using the Wilcoxon test, and the Mann-Whitney. Wilcoxon's analysis showed that breastfeeding counseling training had an influence on the knowledge (p=0.000), attitudes (p=0.001), and skills (p=0,000) of the breastfeeding support group. Breastfeeding counseling training is effective in increasing knowledge, attitudes, and skills. It was expected that the Health Department and Public Health Center implement it regularly with wider coverage and automatically create a new breastfeeding support group.